Long-term patterns (1980-2008) in the structure of a rocky-bottom macrobenthic community in Smeerenburgfjord, northwest Svalbard : assessment of density and cover using image analysis - Kortsch, Susanne (Universitetet i Tromsø, 2010)
Long-term patterns (1980-2008) in the structure of a macrobenthic sublittoral community on the rocky-bottom of a high Arctic fjord (Smeerenburgfjord) in northwest Svalbard were investigated using image analysis of underwater photographs from a permanently marked locality. Species composition revealed the locality to be characterized by calcareous algae, various brown- and red-algae, and several conspicuous sessile and colonial filter feeders. The most important biotic factors shaping the benthic community were competition for space and the low number of predatory species. Environmental factors regarded as having great impact on the community structure were the vertical orientation of the substrate and intermediate to strong water currents. Sea surface temperature (SST), West Spitsbergen Current (WSC) temperature and salinity, North Atlantic Oscillation (NAO) and sea ice cover (SIC) were tested as predictors for the variation in community structure between years. All together the environmental predictors accounted for 69% of the variation. Particularly, high correlations were found between the community structure, and the temperature gradients (SST and WSC) and SIC. High correlations were also found between the Shannon-Wiener Biodiversity (H’) index and the SST (0.7) and SIC (-0.66). The most pronounced changes in community structure occurred after 1994. Among the species associated with these changes are: brown- and red-algae, S. spirorbis and Bryozoans. The most remarkable and persistent change observed was the expansion of leaf-like macroalgae, increasing from 1% cover in 1980 to 40% cover in 2008.